ANALISIS FAKTOR EKSPLOITASI HUTAN DI IUPHHK-HA PT BINA MULTI ALAM LESTARI - Yudha Galoh Kelana Putra; Zainal Abidin; Lusyiani Lusyiani (Universitas Lambung Mangkurat, 2021)
The exploitation factor is one of the important parameters in harvesting forest products in accordance with the 0.70 quota set by the Ministry of Forestry. The method used in this study refers to several sources, in calculating the exploitation factor using a formula based on